Metabolit Bakteri Endofit Asal Tanaman Kacang Tanah sebagai Penghambat Pertumbuhan Aspergillus flavus - Nela Zahara; Bonny Poernomo Wahyu Soekarno; Abdul Munif (Jurnal Fitopatologi Indonesia, 2018)
eanut (Arachis hypogeae) is considered as important crop in Indonesia and domestic demands to peanut tend to increase recently. Infection of fungal seedborne, Aspergillus flavus, may downgrade peanut seed quality. Research was conducted to evaluate the application of secondary metabolite produced by endophytic bacteria for controlling A. flavus. The methodologies involved isolation A. flavus and endophytic bacteria from the plant tissue of peanut, hypersensitive test of endophytic bacteria, inhibition test of endophytic bacteria against A. flavus, extraction and examination of secondary metabolite from endophytic bacteria, seed treatment using extracted secondary metabolite, and molecular identification of the bacteria. Based on hypersensitive test, 37 isolates of endophytic bacteria were identified as non pathogenic. Further screening by dual culture test found 3 isolates with high inhibition activity, i.e. BE2B2-1 (71.64%), BE2B2-2 (69.05%), and BE2B2-5 (62.25%). Molecular identification based on nucleotide sequencing of 16S rRNA showed that BE2B2-1, BE2B2-2, and BE2B2-5 were Enterobacter sp., Bacillus sp., and Acinetobacter sp., respectively. Metabolite from Enterobacter sp. has the highest antimicrobial activity (61.70%) against A. flavus in in vitro test, highest infection inhibition (77.22%) in growing-on test, and highest increasing of seed germination rate (4.25%). This finding indicated the potential of secondary metabolites from endophyte bacteria to suppress infestation of A. flavus.